The Effect of Waiting Time and Employee Services on The Patient Decision to Choose A Hospital and Its Impact on Patient Satisfaction - Fadil, Emilda Faisal (International Humanities and Applied Science Journal, 2020)
To overcome the competition in the hospital business, Annisa Hospital conducts research aimed at knowing the influence of waiting time and employee services to the patient's decision to choose a hospital and its impact on patient satisfaction. With the validity and reality test, the analysis of PLS (Partial Least Square) is processed using Smart PLS (partial least square) version 3.0 software. The waiting time relationship and the decision to choose the hospital have a value of 0053, a T-statistic of 0374, and a P-Value of 0708, (H1) was rejected. Relationship waiting time and patient satisfaction with 0.021 value, T-Statistic of 0357, and P-Value of 0721, (H2) declined. Employee service relations and decision to choose a hospital with a value of 0612, T-Statistic of 8,850, and P-Value amounting to 0.000, (H3) is accepted. Employee service relationship and patient satisfaction with a value of 0354, T-Statistic of 4,294, and P-Value of 0.000, (H4) are accepted. The decision relationship chooses hospitals and patient satisfaction with a value of 0611, T-Statistic of 7,837, and P-Value of 0.000, (H5) are accepted. To intervening variables for the decision of choosing the hospital cannot irradiate the waiting time relationship with patient satisfaction, (H6) rejected. The decision to choose the hospital to fully complete the employee's service relationship with patient satisfaction, (H7) received.